2020
DOI: 10.1101/2020.07.28.224808
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased influence of prior choices on perceptual decisions in autism

Abstract: Autism spectrum disorder (ASD) manifests sensory and perceptual atypicalities. Recent theories suggest that these may reflect a reduced influence of prior information in ASD. Although many studies have not found reduced long-term priors ASD, some have found reduced adaptation to recent sensory stimuli. However, the effects of recent prior stimuli and prior perceptual choices can counteract one-another. Here, we investigated this using two different tasks (in two different cohorts): (i) visual location discrimi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 60 publications
0
6
0
Order By: Relevance
“…However, contrary to these claims of uniformly weak priors (Pellicano & Burr, 2012), there is evidence for intact use of perceptual expectations and prior belief in ASD, for both natural and task-related priors (e.g. Feigin et al, 2021; Hadad & Schwartz, 2019; Manning et al, 2017; Van de Cruys et al, 2021). Several studies report that individuals with autism often develop very strong priors or expectations in particular contexts.…”
Section: Introductionmentioning
confidence: 61%
“…However, contrary to these claims of uniformly weak priors (Pellicano & Burr, 2012), there is evidence for intact use of perceptual expectations and prior belief in ASD, for both natural and task-related priors (e.g. Feigin et al, 2021; Hadad & Schwartz, 2019; Manning et al, 2017; Van de Cruys et al, 2021). Several studies report that individuals with autism often develop very strong priors or expectations in particular contexts.…”
Section: Introductionmentioning
confidence: 61%
“…In the context of numerical problem solving, it is plausible that repeated practice with rule-based strategies may result in an overreliance of this strategy in children with ASD which persists beyond initial training, while TD children progress into memory-based strategies. Consistent with this view, it has been shown that individuals with ASD show increased influence of prior choices on subsequent decisions (Feigin et al, 2021). It is possible that while more efficient execution of rule-based strategies may contribute to preserved or enhanced generalization in children with ASD, persistence with same strategies may hinder learning in situations where flexible use of different problem-solving strategies is advantageous.…”
Section: Discussionmentioning
confidence: 72%
“…Moreover, a recent study showed that in a localization task, individuals with ASD have an enhanced consistency bias and tend to make the same decisions over trials. These studies suggest an inflexible decision rule in ASD (Feigin et al, 2021).…”
Section: Decision Rule In Asdmentioning
confidence: 71%